Designing BIPA’s Teaching Material: Inserting The Local Wisdom? - Candradewi Wahyu Anggraeni; Endah Ratnaningsih (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
This study aims to explain the teaching materials used and needed in BIPA (Bahasa Indonesia bagi Penutur Asing) learning and to develop BIPA teaching materials based on local wisdom as pedagogical content knowledge at Tidar University. BIPA Learning at Tidar University is facilitated by the Integrated Service Unit for Language Centre. BIPA learning at University Tidar is still relatively new and still requires further research to find out the needs of foreign learners studying here. Teaching materials that have been used need to be developed by paying attention to local wisdom as pedagogical content knowledge, generally in Indonesia and specifically in Magelang, so that learners have a better understanding about the concept of Indonesian language by paying attention to the values or characters contained in the learning material. This research uses research and development methods (Research & Development). The subjects of this study were BIPA instructors and learners at Tidar University. The object of this research is the BIPA teaching materials document which will be developed using the local wisdom base as pedagogical content knowledge. Data collection techniques used in this study are questionnaire and interview techniques. The findings show that teaching material for the local wisdom as the pedagogical content knowledge is important to be inserted in BIPA teaching and learning process.